Clinical and Radiological Profile of Patients with Polycystic Ovary Syndrome - Afrasyab Khalil, Tahir Ghaffar, Asifa Abdul Jabbar (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The current study aimed to assess the symptomatology, clinical features, and ultrasound findings in individuals with polycystic ovarian syndrome (PCOS). Methodology: A cross-sectional research was undertaken at the Department of Gynaecology at the Medical Teaching Institute, Hayatabad Medical Complex, Peshawar MTI, HMC between 1st January 2021 to 31 December 2022. Hundred patients of the reproductive age group presenting in Gynecology outpatient departments with signs of PCOS meeting the inclusion criteria were selected for the study. A thorough history and examination were conducted. Laboratory and ultrasound examinations supported the PCOS diagnosis. Results: A total of 109 patients with a mean age of 26.02 ± 8.66 years were assessed. 13 (11.93%) were overweight, and 44 (40.37%) were classified as obese. The mean BMI was 26.98 ± 7.24 kg/m2. 75 (68.8%) individuals reported having menstrual irregularities. Out of these, oligomenorrhea was reported in 56 (51.38%) and amenorrhoea was revealed in 19 (17.43%) patients. 80 (73.39%) reported having overgrowth of hair. Infertility was reported in 60 (55.05%) patients. Majority of the patients had high cholesterol, luteinizing hormone and testosterone. Conclusion: Obesity, hirsutism, and irregular periods were the most prevalent clinical manifestations of PCOS. Hormonal irregularities were quite common. Many PCOS patients can be identified by taking a thorough medical history and completing a thorough physical examination. Keywords: PCOS, diagnosis, obesity, amenorrhea, menorrhagia